1990
DOI: 10.1002/pola.1990.080280116
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a thermally phase‐separating copolymer, poly(N‐isopropylacrylamide‐co‐N‐acryloxysuccinimide), with a controlled number of active esters per polymer chain

Abstract: N‐isopropylacrylamide and N‐acryloxysuccinimide have been copolymerized in various mixtures of terrahydrofuran and toluene using azobisisobutyronitrile as initiator. Polymerization has been conducted for 24 h at 50°C under a slightly positive pressure of nitrogen. The copolymers were assayed for active ester content by measuring the UV absorbance (259 nm) of N‐hydroxysuccinimide anion, generated by reacting the copolymers with N‐isopropylamine in dimethylformamide and dissolving the resulting mixture in 0.1M H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 13 publications
4
26
0
Order By: Relevance
“…Two different GPC setups were used for our studies, but still, it was very difficult to receive reliable values for molar masses. The strong tendency for the formation of hydrogen bonding, as well as the temperature dependent phase behavior cause strong problems in GPC analysis [18,53] and thus, the values reported should be regarded with great caution even though we obtained a reasonable agreement between values obtained from runs on different systems. GPC analysis usually has been conducted on protected glycopolymers in order to avoid (or reduce) undesired interaction with column material.…”
Section: (A) Shows the Plot Of Ln([m] 0 /[M])supporting
confidence: 67%
See 1 more Smart Citation
“…Two different GPC setups were used for our studies, but still, it was very difficult to receive reliable values for molar masses. The strong tendency for the formation of hydrogen bonding, as well as the temperature dependent phase behavior cause strong problems in GPC analysis [18,53] and thus, the values reported should be regarded with great caution even though we obtained a reasonable agreement between values obtained from runs on different systems. GPC analysis usually has been conducted on protected glycopolymers in order to avoid (or reduce) undesired interaction with column material.…”
Section: (A) Shows the Plot Of Ln([m] 0 /[M])supporting
confidence: 67%
“…[15,16] Therefore, many research groups started to synthesize glycopolymers. [17,18] Ohno and Fukuda [19,20] have pioneered the synthesis of glycopolymers via both nitroxide-mediated (NMRP) and atom transfer radical polymerization (ATRP) of the corresponding glycomonomers. Recently, various polymerization techniques were used to synthesize glycopolymers aiming for well-defined structures.…”
Section: Full Papermentioning
confidence: 99%
“…Even though these systems (Onyx ® (EVOH) received FDA approval for clinical use, several studies about solvent toxicity have been reported. [2,3] Onyx also requires, on average, one and a half hours for injection into an aneurysm. 2 Therefore, a waterborne polymer system with no adhesion to the tissue and that can be applied and gelled in less than 10 min would be a superior alternative.…”
Section: In Vitro and In Vivo Demonstration Of Physically And Chemicamentioning
confidence: 99%
“…[3] Briefly, NIPAAm and NASI were dissolved in anhydrous THF (10 wt.%). AIBN was added after 15 min of nitrogen purging and the reaction proceeded for 24 h at 65 C. The polymer solution was precipitated in an excess of diethyl ether, filtered, and vacuum-dried.…”
Section: Synthesis Of Poly(nipaam-co-cysoet) [Polymer Ii]mentioning
confidence: 99%
“…Allan Hoffman, taking advantage of his rich experience in biomolecule immobilization, has therefore collaborated in a number of projects with biotechnological applications in mind. Hoffman's career took a distinctly different turn at this juncture because he was able to establish productive collaborations with colleagues in the biotechnology industry, including John Priest, Robert Nowinski, and Nobuo Monji, that resulted in the development of some novel phase separation immunoassays employing thermally sensitive hydrogels [76,77] and active esters [78] for separation and immobilization, respectively. Patentable inventions, as well as publications, resulted from this work.…”
Section: Materials For Biotechnology Applicationsmentioning
confidence: 99%